"You need a phone and camera in your bag before you go out!": Children's play with imaginative technologies. (3rd April 2019) - Bird, Jo
Abstract: Early childhood settings value play as the way young children learn and educators encourage children's re‐enactment of cultural practices in the imaginative play spaces provided. From a cultural‐historical perspective, children expect these imaginative play spaces to contain objects from their social contexts, but what happens when technologies are not provided? The aim of this study was to explore children's imaginative play involving working and imaginative technologies within two kindergartens (the year before formal schooling). Imaginative play spaces are designed to replicate social situations relevant to the cultural context in which they occur and as technologies increase in society, their proliferation is reflected within early childhood settings. Understanding the role that imaginative technologies can play in children's digital literacy learning is important for the early childhood field. Also, these devices are often absent from literature and overlooked in conversations about children's digital participation. The findings show how the children engaged with the imaginative technologies and raises questions around the influence of these technologies on children's imaginative play and their technological understandings. The findings have implications for educators' understandings of children's play with technologies and the objects they provide in an era where children's lives are increasingly immersed in technology.